An electrode sheet, a method for manufacturing the same, and a lithium ion battery
Patent Information
- Application Number
- CN202511779470.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-28
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-11-28
AI Technical Summary
[0002]目前,在现有的锂离子电池制造技术中,通常通过采用转移涂布或喷涂等方式在集流体上涂覆活性浆料,再经烘干、激光切极耳制备极片,这种方法在激光切割极耳过程中容易产生毛刺,使极片在卷绕组装或使用过程中易刺穿或者划破隔膜造成电池内部短路,从而导致锂电池起火、爆炸等风险,影响产品质量与安全性
[0026]以上制备方法中,通过在集流体基材上至少极耳区的表面设置氢氧化镁层,可对极耳模切进行保护,利于改善极耳模切处截面的毛刺水平,甚至防止切割极耳时产生毛刺。其中,采用低颗粒度的氢氧化镁颗粒配制氢氧化镁浆料构建氢氧化镁层,可使氢氧化镁层中的氢氧化镁颗粒粘结更紧密,使氢氧化镁层的整体形貌更加规则,后续激光模切极耳时,能够缩短集流体基材的受热影响时间,降低金属毛刺生产的风险;制备氢氧化镁层时,控制氢氧化镁层的表面粗糙度为1.2μm~2μm,具有低表面粗糙度的氢氧化镁层在后续极耳模切过程中,受激光切割时,氢氧化镁层各区域受热作用的形变一致性高,可均匀、快速的传导热量至集流体基材,缩短基材受热影响时间,进一步降低产生毛刺的概率,改善毛刺水平;另外,制备氢氧化镁层时,同时控制氢氧化镁层的导热系数为0.2 W/(m·K)~1.0W/(m·K),进而氢氧化镁层的低导热系数可改善层体韧性,使其不易脆裂,有效改善极片上经过激光模切后的极耳模切截面毛刺水平,从而提高产品极片的加工良率和安全可靠性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and in particular to an electrode, its preparation method, and a lithium-ion battery. Background Technology
[0002] Currently, in existing lithium-ion battery manufacturing technologies, active slurry is typically coated onto the current collector using methods such as transfer coating or spraying, followed by drying and laser cutting of the tabs to prepare the electrode sheets. This method is prone to generating burrs during laser cutting of the tabs, which can easily puncture or tear the separator during winding, assembly, or use, causing internal short circuits in the battery. This can lead to risks such as lithium battery fires and explosions, affecting product quality and safety. To address this issue, major manufacturers apply a ceramic coating near the tab cutting location to protect the tabs during die-cutting. However, the protective effect of this method is currently limited, and the resulting electrode sheets still pose safety hazards. When the burr size is larger than the thickness of the ceramic coating, there is still a risk of puncturing the separator, causing a short circuit, and potentially igniting the battery cell. Summary of the Invention
[0003] This invention aims to solve at least one of the technical problems existing in the prior art. To this end, this invention proposes an electrode, a method for preparing the same, and a lithium-ion battery.
[0004] In a first aspect, the present invention provides an electrode comprising: A current collector, the edge of which has tabs; A magnesium hydroxide layer is disposed on at least one side surface of the current collector and covers at least a portion of the surface of the electrode tab; the magnesium hydroxide layer comprises magnesium hydroxide particles with a particle size Dv50 of 0.2 μm to 1.5 μm; the surface roughness of the magnesium hydroxide layer is 1.2 μm to 2 μm, and the thermal conductivity is 0.2 W / (m·K) to 1.0 W / (m·K); An active material layer is disposed on at least one side surface of the current collector and is adjacent to or partially overlaps with the magnesium hydroxide layer.
[0005] The electrode sheet according to embodiments of the present invention has at least the following beneficial effects: The electrode sheet, by providing a magnesium hydroxide layer on at least a portion of the surface of the current collector's upper tab, can protect the tab from die-cutting, wherein the magnesium hydroxide layer is controlled to have a low thermal conductivity (0.2). Compared to magnesium hydroxide layers with high thermal conductivity (W / (m·K)~1.0W / (m·K)), this improves the toughness of the layer, making it less brittle and reducing the burr level after heat treatment. By controlling the surface roughness of the magnesium hydroxide layer to be low (i.e., 1.2μm~2μm), the deformation consistency of the magnesium hydroxide layer under heat treatment is high during laser cutting, which can uniformly and quickly conduct heat to the current collector substrate, shorten the heat treatment time of the substrate, further improve the burr level, and reduce the probability of metal burrs. In addition, the magnesium hydroxide layer is constructed using low particle size (Dv50 of 0.2μm~1.5μm), and the magnesium hydroxide particles in the magnesium hydroxide layer are more tightly bonded, making the overall morphology of the magnesium hydroxide layer more regular. When subjected to laser heat treatment, it can shorten the heat treatment time of the current collector substrate and reduce the risk of metal burrs. Therefore, by setting a magnesium hydroxide layer on at least a portion of the electrode tab surface and strictly controlling the particle size of the magnesium hydroxide layer, as well as the surface roughness and thermal conductivity of the magnesium hydroxide layer, the burr level of the electrode tab die-cutting section after laser die-cutting can be effectively improved, thereby increasing the processing yield and safety reliability of the product electrode.
[0006] The thermal conductivity of the magnesium hydroxide layer can be measured using the hot-wire method. Specifically, a metal wire (hot wire) is embedded in the sample, and after heating with electricity, the temperature rise over time is recorded. The thermal conductivity is calculated from the temperature rise rate. The surface roughness of the magnesium hydroxide layer can be measured using a white light interferometer, referencing standard ISO 25178. The height difference on the coating surface is analyzed using the interference fringes of light to reconstruct the three-dimensional morphology. The particle size Dv50 of the magnesium hydroxide particles can be measured using a laser particle size analyzer.
[0007] The particle size Dv50 of magnesium hydroxide particles can be any value or a range of any two of the following: 0.2μm, 0.3μm, 3.5μm, 0.4μm, 0.5μm, 0.55μm, 0.6μm, 0.65μm, 0.7μm, 0.75μm, 0.8μm, 0.85μm, 0.9μm, 1μm, 1.2μm, 1.35μm, 1.4μm, and 1.5μm. If the particle size Dv50 of magnesium hydroxide is too large (e.g., >1.5μm), it tends to result in a thicker and denser magnesium hydroxide layer, increasing cutting resistance during die cutting. This can easily lead to incomplete cutting and larger metal burrs on the current collector. Conversely, if the particle size D50 is too small, the resulting magnesium hydroxide layer is too thin, resulting in reduced mechanical strength and protective properties. It cannot effectively protect the current collector, and during die cutting, it acts almost directly on the current collector, increasing burrs. Therefore, by controlling the particle size Dv50 of magnesium hydroxide within the above range, sufficient strength and protection of the magnesium hydroxide layer are ensured without excessively increasing the cutting difficulty, thus effectively controlling burrs.
[0008] Furthermore, the surface roughness of the magnesium hydroxide layer can be any value or a range of any two of the following: 1.2 μm, 1.3 μm, 1.45 μm, 1.5 μm, 1.6 μm, 1.65 μm, 1.7 μm, 1.8 μm, 1.9 μm, and 2 μm. If the surface roughness of the magnesium hydroxide layer is too large, the laser energy cannot be absorbed and conducted evenly, which will lead to instability during laser cutting and increased burrs. If the surface roughness of the magnesium hydroxide layer is too small, its heat conduction is rapid and concentrated, the interaction time between the laser and the material during die cutting is extremely short, the cutting process is difficult to control, and burrs are prone to increase.
[0009] The thermal conductivity of the magnesium hydroxide layer can be any value or a range of any two of the following: 0.2 W / (m·K), 0.25 W / (m·K), 0.3 W / (m·K), 0.36 W / (m·K), 0.4 W / (m·K), 0.45 W / (m·K), 0.5 W / (m·K), 0.52 W / (m·K), 0.55 W / (m·K), 0.6 W / (m·K), 0.65 W / (m·K), 0.7 W / (m·K), 0.8 W / (m·K), 0.85 W / (m·K), 0.9 W / (m·K), 0.95 W / (m·K), and 1.0 W / (m·K). If the thermal conductivity of the magnesium hydroxide layer is too high, the die-cutting time is extremely short, the process is difficult to control, burrs increase, and the toughness of the magnesium hydroxide layer deteriorates, making it prone to brittleness and forming even larger burrs after being heated. If the thermal conductivity is too low, the die-cutting time increases, the heating effect is greater, and burrs are more likely to increase. Controlling the thermal conductivity of the magnesium hydroxide layer to have a low thermal conductivity can improve the above problems and reduce the burr level.
[0010] In some embodiments of the present invention, the product of the thermal conductivity (in W / (m·K)) of the magnesium hydroxide layer and the particle size Dv50 (in μm) of the magnesium hydroxide particles is less than or equal to the surface roughness (in μm) of the magnesium hydroxide layer. From the perspective of die-cutting process input and output, surface roughness is affected by material particle size and material thermal conductivity. If the product of the magnesium hydroxide particle size D50 and the thermal conductivity of the magnesium hydroxide layer is too large, it means that either the heat conduction is too fast (thermal conductivity is too high), or the particles are too large (D50 is too large), or both. This will exacerbate the aforementioned adverse effects, resulting in excessively rapid heat loss and high cutting resistance. At this time, even if the surface roughness itself is within the acceptable range, it is usually difficult to offset the heat management imbalance and increased cutting difficulty caused by excessively high thermal conductivity and excessively large particles. This mismatch between parameters will disrupt the dynamic balance of heat conduction, absorption and dissipation during laser cutting, ultimately leading to burr deterioration. Furthermore, by limiting the thermal conductivity and thermal conductivity in the above manner, the surface roughness of the magnesium hydroxide layer can be controlled, thereby reducing the burr level after die-cutting.
[0011] In some embodiments of the present invention, the burr length of the cross section of the electrode tab die-cutting part is less than or equal to 3.5 μm.
[0012] In some embodiments of the present invention, the magnesium hydroxide layer is disposed on one side surface of the current collector and covers at least a portion of the surface of the tab. Specifically, the magnesium hydroxide layer may be designed to be disposed on one side surface of the current collector and cover part or all of the surface of the tab; wherein, the part of the surface of the tab may include the edge surface of the tab, so as to facilitate the action of the magnesium hydroxide layer during laser die-cutting, thereby protecting the die-cut tab, improving the burr level, and reducing the probability of burr generation during die-cutting; if the magnesium hydroxide layer is designed to cover the entire surface of the tab, it can accelerate the heat conduction during laser cutting, shorten the heat-affected time of the current collector substrate, and reduce the probability of burr generation. Further, in some embodiments, the magnesium hydroxide layer may be designed to be disposed at the edge of the current collector and adjacent to or partially overlapping with the active material layer.
[0013] In some embodiments of the present invention, the magnesium hydroxide layer is disposed on both sides of the current collector and covers at least a portion of the surface of the tab, thereby further improving the burr level at the tab die-cutting section and reducing the probability of burr generation. Specifically, the magnesium hydroxide layer can be designed to be disposed on both sides of the current collector and cover part or all of the surface of the tab, wherein the part of the surface of the tab may include the edge surface of the tab. Alternatively, the magnesium hydroxide layer on both sides of the current collector can be designed to cover part or all of the surface of the tab, or the magnesium hydroxide layer on one side of the current collector can cover part of the surface of the tab, while the magnesium hydroxide layer on the other side covers the entire surface of the tab.
[0014] In some embodiments of the present invention, the tab portion at the edge of the current collector is configured to connect to an external tab.
[0015] In some embodiments of the present invention, the tab portion at the edge of the current collector is configured as a tab.
[0016] In addition, the electrode tabs at the edge of the current collector can be one or more (such as 2, 3, 4, 5, 6, 8, etc.).
[0017] In some embodiments of the present invention, the magnesium hydroxide layer further includes a binder.
[0018] In some embodiments of the present invention, the magnesium hydroxide layer comprises 5 wt% to 25 wt% magnesium hydroxide particles and 75 wt% to 95 wt% binder. For example, the content of magnesium hydroxide particles in the magnesium hydroxide layer may be any value or a range of any two of 5 wt%, 8 wt%, 10 wt%, 12 wt%, 13 wt%, 15 wt%, 16 wt%, 18 wt%, 20 wt%, 23 wt%, and 25 wt%; the content of binder may be any value or a range of any two of 75 wt%, 77 wt%, 80 wt%, 82 wt%, 84 wt%, 85 wt%, 87 wt%, 88 wt%, 90 wt%, 92 wt%, and 95 wt%.
[0019] In some embodiments of the present invention, the adhesive is selected from at least one of polyvinylidene fluoride (PTFE) and polyacrylonitrile (PAN).
[0020] In some embodiments of the present invention, the active material layer is disposed on both sides of the current collector.
[0021] In some embodiments of the present invention, the electrode is a positive electrode, the current collector is a positive current collector, and the active material layer is a positive active material layer.
[0022] The positive electrode current collector can be at least one of aluminum, copper, platinum, and silver. The positive electrode active material layer includes a positive electrode active material, which can be LiCoO2, LiMn2O4, Li2MnO3, Li2CrO4, LiNiO2, or LiNiO2. 0.5 Mn 1.5The positive electrode active material layer may include at least one of O4, LiFePO4, LiMnPO4, and LiCoPO4. The positive electrode active material layer may also include at least one of superconducting carbon black (super p), graphite, carbon black, carbon fiber, and carbon nanotubes; the positive electrode active material layer may also include at least one of polyvinylidene fluoride (PVDF), epoxy resin, styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC).
[0023] In some embodiments of the present invention, the electrode is a negative electrode, the current collector is a negative electrode current collector, and the active material layer is a negative electrode active material layer.
[0024] The negative electrode current collector can be at least one of copper, nickel, iron, silver, titanium, and platinum. The negative electrode active material layer includes a negative electrode active material, which can be a lithium-intercalable carbon material or a non-carbon material. The carbon material can be at least one of natural graphite, artificial graphite, soft carbon, hard carbon, or mesophase carbon microspheres. The non-carbon material can be at least one of lithium, elemental silicon, silicon compounds, elemental tin, tin compounds, lithium titanium phosphate, or lithium titanate. Furthermore, the negative electrode active material layer may also include a conductive agent, which can be at least one of graphite, carbon black, graphene, carbon nanotubes, or carbon nanofibers. The negative electrode active material layer may also include a binder, which can be at least one of styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), or polyvinyl alcohol (PVA).
[0025] A second aspect of the present invention provides a method for preparing any of the aforementioned electrode sheets, comprising the following steps: Take a current collector substrate and mark the tab area on the current collector substrate; A magnesium hydroxide slurry is prepared by mixing magnesium hydroxide particles with a particle size Dv50 of 0.2 μm to 1.5 μm with a solvent. The magnesium hydroxide slurry is then coated onto the surface of at least the tab region of the current collector substrate to prepare a magnesium hydroxide layer. The surface roughness of the magnesium hydroxide layer is controlled to be 1.2 μm to 2 μm, and the thermal conductivity is 0.2 W / (m·K) to 1.0 W / (m·K). An active material layer is disposed on the current collector substrate, and the active material layer is adjacent to or partially overlaps with the magnesium hydroxide layer; The tab area on the current collector substrate is die-cut using laser die-cutting.
[0026] In the above preparation method, by setting a magnesium hydroxide layer on the surface of at least the tab area on the current collector substrate, the tab die-cutting can be protected, which helps to improve the burr level of the cross-section at the tab die-cutting point and even prevents burrs from being generated during tab cutting. Specifically, using low-particle-size magnesium hydroxide particles to prepare the magnesium hydroxide slurry to construct the magnesium hydroxide layer allows for tighter bonding of the magnesium hydroxide particles in the layer, resulting in a more regular overall morphology of the magnesium hydroxide layer. This shortens the heat-affected time of the current collector substrate during subsequent laser die-cutting of the tab, reducing the risk of metal burr production. When preparing the magnesium hydroxide layer, controlling the surface roughness of the magnesium hydroxide layer to 1.2μm~2μm ensures that the magnesium hydroxide layer with low surface roughness exhibits high uniformity of deformation under heat during subsequent tab die-cutting, allowing for uniform and rapid heat conduction to the current collector substrate, shortening the heat-affected time of the substrate, further reducing the probability of burr generation, and improving the burr level. Additionally, when preparing the magnesium hydroxide layer, the thermal conductivity of the magnesium hydroxide layer is simultaneously controlled to be 0.2. With a thermal conductivity of W / (m·K)~1.0W / (m·K), the low thermal conductivity of the magnesium hydroxide layer can improve the toughness of the layer, making it less brittle and effectively improving the burr level of the electrode tab die-cutting section after laser die-cutting, thereby improving the processing yield and safety reliability of the product electrode.
[0027] In some embodiments of the present invention, the viscosity of the magnesium hydroxide slurry is 2000 mPa·s to 7000 mPa·s, and the purity of the magnesium hydroxide particles is 99.90% to 99.95%. For example, the viscosity of the magnesium hydroxide slurry can be controlled to be any value or a range of any two of the following: 2000 mPa·s, 2300 mPa·s, 2500 mPa·s, 2800 mPa·s, 3000 mPa·s, 3600 mPa·s, 4000 mPa·s, 4500 mPa·s, 5000 mPa·s, 5200 mPa·s, 5500 mPa·s, 6000 mPa·s, 6300 mPa·s, 6500 mPa·s, 6800 mPa·s, and 7000 mPa·s. The purity of magnesium hydroxide particles can be any value or a range of any two of the following: 99.90%, 99.92%, 99.93%, 99.94%, and 99.95%. The purity of magnesium hydroxide particles is expressed as the mass fraction of the particles. The purity of magnesium hydroxide particles can be determined by using XRD to analyze the phase structure of the magnesium hydroxide material, detect the content of impurity elements in the material, and then remove the impurity elements to obtain the purity of the magnesium hydroxide particles.
[0028] The above methods improve the burr level during laser die-cutting of electrode tabs by controlling the viscosity of magnesium hydroxide slurry to 4200 mPa.s ~ 5800 mPa.s and the surface roughness of the magnesium hydroxide layer to 1.2 μm ~ 2 μm. By controlling the purity of magnesium hydroxide particles to 99.90% ~ 99.95% and the thermal conductivity of the magnesium hydroxide layer to 0.2 W / (m·K) ~ 1.0 W / (m·K).
[0029] Generally, for the above magnesium hydroxide slurry, when the viscosity of the magnesium hydroxide slurry is 5800 mPa·s, the surface roughness of the resulting magnesium hydroxide layer is approximately 2 μm; when the viscosity of the magnesium hydroxide slurry is 4700 mPa·s, the surface roughness of the resulting magnesium hydroxide layer is approximately 1.5 μm; and when the viscosity of the magnesium hydroxide slurry is 4200 mPa·s, the surface roughness of the resulting magnesium hydroxide layer is approximately 1.2 μm. When the purity of the magnesium hydroxide particles is 99.95%, the corresponding thermal conductivity of the resulting magnesium hydroxide layer is approximately 1.0 W / (m·K); when the purity of the magnesium hydroxide particles is 99.93%, the corresponding thermal conductivity of the resulting magnesium hydroxide layer is approximately 0.6 W / (m·K); and when the purity of the magnesium hydroxide particles is 99.90%, the corresponding thermal conductivity of the resulting magnesium hydroxide layer is approximately 0.2 W / (m·K).
[0030] In some embodiments of the present invention, the magnesium hydroxide layer raw material further includes a binder. Further, the magnesium hydroxide layer raw material may include 5 wt% to 25 wt% magnesium hydroxide particles and 75 wt% to 95 wt% binder.
[0031] In some embodiments of the present invention, the solvent is an organic solvent. For example, the solvent may be N-methylpyrrolidone (NMP) or other organic solvents.
[0032] In the preparation of the magnesium hydroxide layer, magnesium hydroxide slurry is applied to at least the surface of the tab area on the current collector substrate. Specifically, magnesium hydroxide slurry can be applied to one or both surfaces of the tab area on the current collector substrate, and the surface of the tab area can be partially or completely coated. If partial coating is applied to the surface of the tab area, the coating area includes the tab die-cut position.
[0033] A third aspect of the present invention provides a lithium-ion battery comprising a positive electrode, a negative electrode, and a separator, wherein the separator is sandwiched between the positive electrode and the negative electrode, and the positive electrode and / or the negative electrode are prepared by any of the electrode preparation methods described above or any of the electrode preparation methods described above. Detailed Implementation
[0034] The following will describe the concept and technical effects of the present invention clearly and completely with reference to embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.
[0035] Example 1 This embodiment proposes a positive electrode, which includes a current collector, an active material layer, and a magnesium hydroxide layer. The current collector has tabs at its edge, the active material layer is disposed on both sides of the current collector, and the magnesium hydroxide layer is disposed on the edge tab surface of the current collector and adjacent to the active material layer. The magnesium hydroxide layer comprises 80 wt% magnesium hydroxide particles and 20 wt% PVDF binder, the magnesium hydroxide particles having a particle size Dv50 of 0.5 μm; the surface roughness of the magnesium hydroxide layer is 2 μm, and its thermal conductivity is 0.5 W / (m·K).
[0036] The positive electrode is prepared by a method including the following steps: Take a copper foil substrate for the current collector and mark out the tab area on the copper foil substrate for the current collector; 80 wt% magnesium hydroxide particles (particle size Dv50 of 0.5 μm, purity of 99.90%) and 20 wt% PVDF binder were mixed with NMP solvent to prepare a magnesium hydroxide slurry with a viscosity of 5800 mPa·s. The magnesium hydroxide slurry was then coated on both sides of the tab area of the copper foil on the current collector substrate, with a single-sided coating thickness of 15 μm. After drying, a magnesium hydroxide layer was obtained, which had a surface roughness of 2 μm and a thermal conductivity of 0.2 W / (m·K). Take 98wt% of active material lithium cobalt oxide, 1wt% of binder PVDF and 1wt% of conductive agent carbon black, mix with solvent to prepare active slurry; then coat the active slurry onto the current collector substrate and adjacent to the magnesium hydroxide layer, and dry to obtain the active material layer; Laser die-cutting was used to cut the tab area on the current collector substrate. The die-cutting power was controlled at 80W and the frequency was controlled at 1000Hz to obtain the positive electrode sheet.
[0037] The cross-section of the electrode tab die-cutting point on the positive electrode sheet was observed using a two-dimensional microscope, and the size of the metal burr protruding from the current collector substrate was detected. The burr length of the cross-section of the electrode tab die-cutting point on the positive electrode sheet in this embodiment was found to be 0.1 μm.
[0038] Example 2 This embodiment provides a positive electrode sheet, which differs from Example 1 in that: the magnesium hydroxide particles in the magnesium hydroxide layer of this embodiment have a particle size Dv50 of 1 μm. Correspondingly, in the preparation method of the positive electrode sheet, magnesium hydroxide particles with a particle size Dv50 of 1 μm and a purity of 99.90% are used instead of magnesium hydroxide particles with a particle size Dv50 of 0.5 μm and a purity of 99.90% in Example 1 during the preparation of the magnesium hydroxide layer. Other material configurations, structures, and preparation methods are basically the same as in Example 1.
[0039] Using a burr inspection method similar to that in Example 1, the burr length at the cross-section of the positive electrode tab die-cutting point in this embodiment was found to be 0.2 μm.
[0040] Example 3 This embodiment provides a positive electrode sheet, which differs from Example 1 in that: the magnesium hydroxide particles in the magnesium hydroxide layer of this embodiment have a particle size Dv50 of 0.8 μm. Correspondingly, in the preparation method of the positive electrode sheet, magnesium hydroxide particles with a particle size Dv50 of 0.8 μm and a purity of 99.90% are used instead of magnesium hydroxide particles with a particle size Dv50 of 0.5 μm and a purity of 99.90% in Example 1 during the preparation of the magnesium hydroxide layer. Other material configurations, structures, and preparation methods are basically the same as in Example 1.
[0041] Using a burr inspection method similar to that in Example 1, the burr length at the cross-section of the positive electrode tab die-cutting point in this embodiment was found to be 0 μm.
[0042] Example 4 This embodiment provides a positive electrode sheet, which differs from Example 1 in that: the magnesium hydroxide particles in the magnesium hydroxide layer of this embodiment have a particle size Dv50 of 0.2 μm. Correspondingly, in the preparation method of the positive electrode sheet, magnesium hydroxide particles with a particle size Dv50 of 0.2 μm and a purity of 99.90% are used instead of magnesium hydroxide particles with a particle size Dv50 of 0.5 μm and a purity of 99.90% in Example 1 during the preparation of the magnesium hydroxide layer. Other material configurations, structures, and preparation methods are basically the same as in Example 1.
[0043] Using a burr inspection method similar to that in Example 1, the burr length at the cross-section of the positive electrode tab die-cutting point in this embodiment was found to be 2 μm.
[0044] Example 5 This embodiment provides a positive electrode sheet, which differs from Example 1 in that: the magnesium hydroxide particles in the magnesium hydroxide layer of this embodiment have a particle size Dv50 of 1.3 μm. Correspondingly, in the preparation method of the positive electrode sheet, magnesium hydroxide particles with a particle size Dv50 of 1.3 μm and a purity of 99.90% are used instead of magnesium hydroxide particles with a particle size Dv50 of 0.5 μm and a purity of 99.90% in Example 1 during the preparation of the magnesium hydroxide layer. Other material configurations, structures, and preparation methods are basically the same as in Example 1.
[0045] Using a burr inspection method similar to that in Example 1, the burr length at the cross-section of the positive electrode tab die-cutting point in this embodiment was found to be 2 μm.
[0046] Example 6 This embodiment provides a positive electrode sheet, which differs from Embodiment 1 in that: the magnesium hydroxide particles in the magnesium hydroxide layer of this embodiment have a particle size Dv50 of 1 μm and a purity of 99.95%, and the thermal conductivity of the magnesium hydroxide layer is 1 W / (m·K). Correspondingly, in the preparation method of the positive electrode sheet, magnesium hydroxide particles with a particle size Dv50 of 1 μm and a purity of 99.95% are used instead of magnesium hydroxide particles with a particle size Dv50 of 0.5 μm and a purity of 99.90% in Embodiment 1 during the preparation of the magnesium hydroxide layer. Other material configurations, structures, and preparation methods are basically the same as in Embodiment 1.
[0047] Using a burr inspection method similar to that in Example 1, the burr length at the cross-section of the positive electrode tab die-cutting point in this embodiment was found to be 2 μm.
[0048] Example 7 This embodiment provides a positive electrode sheet, which differs from Example 1 in that: the magnesium hydroxide particles in the magnesium hydroxide layer of this embodiment have a particle size Dv50 of 1.3 μm and a purity of 99.95%, the surface roughness of the magnesium hydroxide layer is 1.2 μm, and the thermal conductivity is 1 W / (m·K). Correspondingly, in the preparation method of the positive electrode sheet, magnesium hydroxide particles with a particle size Dv50 of 1.3 μm and a purity of 99.95% are used instead of magnesium hydroxide particles with a particle size Dv50 of 0.5 mm and a purity of 99.90% in Example 1 during the preparation of the magnesium hydroxide layer. Furthermore, the amount of NMP solvent used in preparing the magnesium hydroxide slurry is adjusted so that the viscosity of the magnesium hydroxide slurry is 4200 mPa·s. Other material configurations, structures, and preparation methods are basically the same as in Example 1.
[0049] Using a burr inspection method similar to that in Example 1, the burr length at the cross-section of the positive electrode tab die-cutting point in this embodiment was found to be 3 μm.
[0050] Example 8 This embodiment provides a positive electrode sheet, which differs from Embodiment 1 in that: the magnesium hydroxide particles in the magnesium hydroxide layer of this embodiment have a particle size Dv50 of 0.5 μm and a purity of 99.95%, and the thermal conductivity of the magnesium hydroxide layer is 1 W / (m·K). Correspondingly, in the preparation method of the positive electrode sheet, magnesium hydroxide particles with a particle size Dv50 of 0.5 μm and a purity of 99.95% are used instead of magnesium hydroxide particles with a particle size Dv50 of 0.5 mm and a purity of 99.90% in Embodiment 1 during the preparation of the magnesium hydroxide layer. Other material configurations, structures, and preparation methods are basically the same as in Embodiment 1.
[0051] Using a burr inspection method similar to that in Example 1, the burr length at the cross-section of the positive electrode tab die-cutting point in this embodiment was found to be 0.2 μm.
[0052] Example 9 This embodiment provides a positive electrode sheet, which differs from Embodiment 1 in that: the magnesium hydroxide particles in the magnesium hydroxide layer of this embodiment have a particle size Dv50 of 0.5 μm and a purity of 99.95%, the surface roughness of the magnesium hydroxide layer is 1.2 μm, and the thermal conductivity is 1 W / (m·K). Correspondingly, in the preparation method of the electrode sheet, magnesium hydroxide particles with a particle size Dv50 of 0.5 μm and a purity of 99.95% are used instead of magnesium hydroxide particles with a particle size Dv50 of 0.5 μm and a purity of 99.90% in Embodiment 1 during the preparation of the magnesium hydroxide layer. Furthermore, the amount of NMP solvent used in preparing the magnesium hydroxide slurry is adjusted so that the viscosity of the magnesium hydroxide slurry is 4200 mPa·s. Other material configurations, structures, and preparation methods are the same as in Embodiment 1.
[0053] Using a burr inspection method similar to that in Example 1, the burr length at the cross-section of the positive electrode tab die-cutting point in this embodiment was found to be 0.3 μm.
[0054] Example 10 This embodiment provides a positive electrode sheet, which differs from Embodiment 1 in that: the surface roughness of the magnesium hydroxide layer in the positive electrode sheet of this embodiment is 1.2 μm and the thermal conductivity is 0.2 W / (m·K). Correspondingly, in the electrode sheet preparation method, the amount of NMP solvent used to prepare the magnesium hydroxide slurry is adjusted during the preparation of the magnesium hydroxide layer so that the viscosity of the magnesium hydroxide slurry is 4200 mPa·s. Other material configurations, structures and preparation methods are the same as in Embodiment 1.
[0055] Using a burr inspection method similar to that in Example 1, the burr length at the cross-section of the positive electrode tab die-cutting point in this embodiment was found to be 1 μm.
[0056] Example 11 This embodiment provides a positive electrode sheet, which differs from Embodiment 1 in that: the magnesium hydroxide particles in the magnesium hydroxide layer of this embodiment have a particle size Dv50 of 1 μm and a purity of 99.95%, the surface roughness of the magnesium hydroxide layer is 1.2 μm, and the thermal conductivity is 1 W / (m·K). Correspondingly, in the preparation method of the electrode sheet, magnesium hydroxide particles with a particle size Dv50 of 1 μm and a purity of 99.95% are used instead of magnesium hydroxide particles with a particle size Dv50 of 0.5 mm and a purity of 99.90% in Embodiment 1 during the preparation of the magnesium hydroxide layer. Furthermore, the amount of NMP solvent used in preparing the magnesium hydroxide slurry is adjusted so that the viscosity of the magnesium hydroxide slurry is 4200 mPa·s. Other material configurations, structures, and preparation methods are the same as in Embodiment 1.
[0057] Using a burr inspection method similar to that in Example 1, the burr length at the cross-section of the positive electrode tab die-cutting point in this embodiment was found to be 0 μm.
[0058] Example 12 This embodiment provides a positive electrode sheet, which differs from Example 1 in that: the magnesium hydroxide particles in the magnesium hydroxide layer of this embodiment have a particle size Dv50 of 1 μm and a purity of 99.90%, the surface roughness of the magnesium hydroxide layer is 1.2 μm, and the thermal conductivity is 0.2 W / (m·K). Correspondingly, in the preparation method of the electrode sheet, magnesium hydroxide particles with a particle size Dv50 of 1 μm and a purity of 99.90% are used instead of magnesium hydroxide particles with a particle size Dv50 of 0.5 μm and a purity of 99.90% in Example 1 during the preparation of the magnesium hydroxide layer. Furthermore, the amount of NMP solvent used in preparing the magnesium hydroxide slurry is adjusted so that the viscosity of the magnesium hydroxide slurry is 4200 mPa·s. Other material configurations, structures, and preparation methods are the same as in Example 1.
[0059] Using a burr inspection method similar to that in Example 1, the burr length at the cross-section of the positive electrode tab die-cutting point in this embodiment was found to be 0 μm.
[0060] Example 13 This embodiment provides a positive electrode sheet, which differs from Example 1 in that: the magnesium hydroxide particles in the magnesium hydroxide layer of this embodiment have a particle size Dv50 of 0.8 μm and a purity of 99.93%, the surface roughness of the magnesium hydroxide layer is 1.5 μm, and the thermal conductivity is 0.6 W / (m·K). Correspondingly, in the preparation method of the electrode sheet, magnesium hydroxide particles with a particle size Dv50 of 0.8 μm and a purity of 99.93% are used instead of magnesium hydroxide particles with a particle size Dv50 of 0.5 μm and a purity of 99.90% in Example 1 during the preparation of the magnesium hydroxide layer. Furthermore, the amount of NMP solvent used in preparing the magnesium hydroxide slurry is adjusted so that the viscosity of the magnesium hydroxide slurry is 4700 mPa·s. Other material configurations, structures, and preparation methods are the same as in Example 1.
[0061] Using a burr inspection method similar to that in Example 1, the burr length at the cross-section of the positive electrode tab die-cutting point in this embodiment was found to be 2 μm.
[0062] Comparative Example 1 This comparative example provides a positive electrode sheet, which differs from Example 1 in that: the magnesium hydroxide particles in the magnesium hydroxide layer of this comparative example have a particle size Dv50 of 0.18 μm. Correspondingly, in the preparation method of the positive electrode sheet, magnesium hydroxide particles with a particle size Dv50 of 0.18 μm and a purity of 99.90% are used instead of magnesium hydroxide particles with a particle size Dv50 of 0.5 μm and a purity of 99.90% in Example 1 during the preparation of the magnesium hydroxide layer. Other material configurations, structures, and preparation methods are basically the same as in Example 1.
[0063] Using a burr inspection method similar to that in Example 1, the burr length at the cross-section of the upper tab die-cut of the positive electrode sheet in this comparative example was found to be 7 μm.
[0064] Comparative Example 2 This comparative example provides a positive electrode sheet, which differs from Example 1 in that: the magnesium hydroxide particles in the magnesium hydroxide layer of this comparative example have a particle size Dv50 of 1.7 μm. Correspondingly, in the preparation method of the positive electrode sheet, magnesium hydroxide particles with a particle size Dv50 of 1.7 μm and a purity of 99.90% are used instead of magnesium hydroxide particles with a particle size Dv50 of 0.5 μm and a purity of 99.90% in Example 1. Other material configurations, structures, and preparation methods are basically the same as in Example 1.
[0065] Using a burr inspection method similar to that in Example 1, the burr length at the die-cut section of the positive electrode sheet in this comparative example was found to be 12 μm.
[0066] Comparative Example 3 This comparative example provides a positive electrode sheet, which differs from Example 1 in that: the magnesium hydroxide particles in the magnesium hydroxide layer of this comparative example electrode sheet have a particle size Dv50 of 0.5 μm and a purity of 99.87%, the surface roughness of the magnesium hydroxide layer is 2 μm, and the thermal conductivity is 0.17 W / (m·K). Correspondingly, in the electrode sheet preparation method, magnesium hydroxide particles with a particle size Dv50 of 0.5 μm and a purity of 99.87% are used instead of magnesium hydroxide particles with a particle size Dv50 of 0.5 μm and a purity of 99.90% in Example 1 during the preparation of the magnesium hydroxide layer. Other material configurations, structures, and preparation methods are the same as in Example 1.
[0067] Using a burr inspection method similar to that in Example 1, the burr length at the cross-section of the upper tab die-cut of the positive electrode sheet in this comparative example was found to be 23 μm.
[0068] Comparative Example 4 This comparative example provides a positive electrode sheet, which differs from Example 1 in that: the magnesium hydroxide particles in the magnesium hydroxide layer of this comparative example electrode sheet have a particle size Dv50 of 0.5 μm and a purity of 99.98%, the surface roughness of the magnesium hydroxide layer is 2 μm, and the thermal conductivity is 1.1 W / (m·K). Correspondingly, in the electrode sheet preparation method, magnesium hydroxide particles with a particle size Dv50 of 0.5 μm and a purity of 99.98% are used instead of magnesium hydroxide particles with a particle size Dv50 of 0.5 μm and a purity of 99.90% in Example 1 during the preparation of the magnesium hydroxide layer. Other material configurations, structures, and preparation methods are the same as in Example 1.
[0069] Using a burr inspection method similar to that in Example 1, the burr length at the cross-section of the upper tab die-cut of the positive electrode sheet in this comparative example was found to be 10 μm.
[0070] Comparative Example 5 This comparative example provides a positive electrode sheet, which differs from Example 1 in that: the surface roughness of the magnesium hydroxide layer in this comparative example electrode sheet is 1 μm, and the thermal conductivity is 0.2 W / (m·K). Correspondingly, in the electrode sheet preparation method, the amount of NMP solvent used to prepare the magnesium hydroxide slurry is adjusted during the preparation of the magnesium hydroxide layer so that the viscosity of the magnesium hydroxide slurry is 4000 mPa·s. Other material configurations, structures, and preparation methods are the same as in Example 1.
[0071] Using a burr inspection method similar to that in Example 1, the burr length at the cross-section of the upper tab die-cut of the positive electrode sheet in this comparative example was found to be 6 μm.
[0072] Comparative Example 6 This comparative example provides a positive electrode sheet, which differs from Example 1 in that: the magnesium hydroxide particles in the magnesium hydroxide layer of this comparative example have a particle size Dv50 of 0.5 μm and a purity of 99.95%, the surface roughness of the magnesium hydroxide layer is 2.4 μm, and the thermal conductivity is 1 W / (m·K). Correspondingly, in the preparation method of the electrode sheet, magnesium hydroxide particles with a particle size Dv50 of 0.5 μm and a purity of 99.95% are used instead of magnesium hydroxide particles with a particle size Dv50 of 0.5 μm and a purity of 99.90% in Example 1 during the preparation of the magnesium hydroxide layer. Furthermore, the amount of NMP solvent used in preparing the magnesium hydroxide slurry is adjusted so that the viscosity of the magnesium hydroxide slurry is 7500 mPa·s. Other material configurations, structures, and preparation methods are the same as in Example 1.
[0073] Using a burr inspection method similar to that in Example 1, the burr length at the cross-section of the upper tab die-cut of the positive electrode sheet in this comparative example was found to be 16 μm.
[0074] The magnesium hydroxide layer setup and preparation process control of the positive electrode sheets in the above embodiments and comparative examples, as well as the burr level of the cross-section at the die-cutting point of the upper electrode tab, are shown in Table 1 below.
[0075] Table 1
[0076] As described above, the positive electrode preparation process of the above embodiments, by setting a magnesium hydroxide layer on the surface of the tab region on the current collector substrate and strictly controlling the particle size of magnesium hydroxide particles in the magnesium hydroxide layer, as well as the surface roughness and thermal conductivity of the magnesium hydroxide layer, can effectively improve the burr level of the tab die-cutting section on the electrode after laser die-cutting, and improve the processing yield and safety reliability of the product electrode.
[0077] In some embodiments of the present invention, a negative electrode sheet is also set up with a structure similar to that of the above embodiments. That is, a magnesium hydroxide layer is set on the surface of the electrode tab area on the current collector electrode tab, and the particle size of magnesium hydroxide particles in the magnesium hydroxide layer, as well as the surface roughness and thermal conductivity of the magnesium hydroxide layer are strictly controlled. It can be understood that similar effects as the positive electrode sheets of the above embodiments can also be achieved. This can effectively improve the burr level of the electrode tab die-cutting section after laser die-cutting, and improve the processing yield and safety reliability of the product electrode sheet.
[0078] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.
Claims
1. An electrode sheet, characterized in that, include: A current collector, the edge of which has tabs; A magnesium hydroxide layer is disposed on at least one side surface of the current collector and covers at least a portion of the surface of the electrode tab; the magnesium hydroxide layer comprises magnesium hydroxide particles with a particle size Dv50 of 0.2 μm to 1.5 μm; the surface roughness of the magnesium hydroxide layer is 1.2 μm to 2 μm, and the thermal conductivity is 0.2 W / (m·K) to 1.0 W / (m·K); An active material layer is disposed on at least one side surface of the current collector and is adjacent to or partially overlaps with the magnesium hydroxide layer.
2. The electrode sheet according to claim 1, characterized in that, The product of the thermal conductivity of the magnesium hydroxide layer and the particle size Dv50 of the magnesium hydroxide particles is less than or equal to the surface roughness of the magnesium hydroxide layer.
3. The electrode sheet according to claim 1, characterized in that, The magnesium hydroxide layer is disposed on both sides of the current collector and covers at least a portion of the surface of the tab; and / or, the active material layer is disposed on both sides of the current collector.
4. The electrode sheet according to claim 1, characterized in that, The surface portion includes the edge surface of the tab portion.
5. The electrode sheet according to any one of claims 1 to 4, characterized in that, The magnesium hydroxide layer also includes a binder.
6. The electrode sheet according to claim 5, characterized in that, The magnesium hydroxide layer comprises 5 wt% to 25 wt% magnesium hydroxide particles and 75 wt% to 95 wt% binder.
7. A method for preparing the electrode sheet according to any one of claims 1 to 6, characterized in that, Includes the following steps: Take a current collector substrate and mark the tab area on the current collector substrate; A magnesium hydroxide slurry is prepared by mixing magnesium hydroxide particles with a particle size Dv50 of 0.2 μm to 1.5 μm with a solvent. The magnesium hydroxide slurry is then coated onto the surface of at least the tab region of the current collector substrate to prepare a magnesium hydroxide layer. The surface roughness of the magnesium hydroxide layer is controlled to be 1.2 μm to 2 μm, and the thermal conductivity is 0.2 W / (m·K) to 1.0 W / (m·K). An active material layer is disposed on the current collector substrate, and the active material layer is adjacent to or partially overlaps with the magnesium hydroxide layer; The tab area on the current collector substrate is die-cut using laser die-cutting.
8. The method for preparing the electrode according to claim 7, characterized in that, The viscosity of the magnesium hydroxide slurry is 4200 mPa·s to 5800 mPa·s, and the purity of the magnesium hydroxide particles is 99.90% to 99.95%.
9. A lithium-ion battery, characterized in that, It includes a positive electrode, a negative electrode, and a separator, wherein the separator is sandwiched between the positive electrode and the negative electrode, and the positive electrode and / or the negative electrode are prepared by the preparation method of the electrode according to any one of claims 1 to 6 or the electrode according to claim 7 or 8.
Citation Information
Patent Citations
Positive plate and preparation method thereof, battery cell and lithium ion battery
CN111554877A
Battery pole piece with ceramic coating on end face and preparation method of battery pole piece
CN118412428A